Development of Computer Based Learning Media about Continuous Variable Transmission (CVT) on Motorcycle Subjects at Vocational High School (SMK) - Agus Budiman (LPPM UNY, 2012)
The purpose of this study was to identify computer-based learning media condition, development process, and proper assessment about CVT. The design of the study was Research and Development. Respondents of this study were eleventh-grade students of Automotive Skills Program at Vocational High School (SMK) in Cilacap Regency of Central Java. Field trials of the media were conducted three times at SMK Dr. Soetomo, at SMK Boedi Oetomo, and at SMK Negeri 2 Cilacap with 36 students of each school. The student's response toward the learning media appropriateness in the media aspect and in the material aspect was collected by closed-questionare. In the media aspect, indicators offeasibility consisted of (1) visual interpretation, (2) visual design, (3) graphics as a visual media, and (4) procedure of media development. Indicators of feasibility in the material aspect were: (1) relevance between the material and the syllabus, and (2) self-learning. The collected data of the learning media appropriateness was analyzed by descriptive statistics in percentages. The result of this initial study showed that based on the media aspect, the media of CVT were in proper condition with a percentage of 86. 96. Meanwhile, based on the material aspect, the media of CVT was not in proper condition with a percentage of 14.28. Viewedfrom the media aspect, the result of the data analysis was in proper condition with percentage of 87.05. Moreover, based on the material aspect, the learning media was in proper condition with a percentage of 58.33%. Keywords: computer-based learning media, continuous variable transmission (CVT), learning media appropriateness, feasibility